2017
DOI: 10.21834/aje-bs.v2i5.224
|View full text |Cite
|
Sign up to set email alerts
|

Public Open Space's Contribution to Quality of Life: Does privatisation matters?

Abstract: Quality of life of people in urban area is the outcome of people interaction with urban environment. Many studies indicate that public open space is one of important urban environment elements which give positive contribution to quality of life. This paper investigates how privatization of public open space affects quality of life of people while many studies show degradation of "publicness" of public space due to privatization. Research ßnding indicates that people keep doing their social activities both in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…The factors are including the space qualities and quantity; the social makeup of the potential users in which they are diverse from the socioeconomic class, sex, life-cycle stage, ethnicity and region; psychological aspects influencing personal preference as well as, the accessibility of domestic against non-domestic spaces, facilities and services (Hester, 1984). Hence, privatization of open space can contribute towards better quality in terms of design exploration, maintenance and management thus influence in higher users' satisfaction index compared to open space that managed by public authority (Nasution & Zahrah, 2012). Previous research that is relevant and related to use pattern study in the context of residential green open spaces and parks will be precisely categorized into three sub-topics, which are activities, passive activity, and active activity.…”
Section: Important Measures Of Community Participation On Use Patternmentioning
confidence: 99%
“…The factors are including the space qualities and quantity; the social makeup of the potential users in which they are diverse from the socioeconomic class, sex, life-cycle stage, ethnicity and region; psychological aspects influencing personal preference as well as, the accessibility of domestic against non-domestic spaces, facilities and services (Hester, 1984). Hence, privatization of open space can contribute towards better quality in terms of design exploration, maintenance and management thus influence in higher users' satisfaction index compared to open space that managed by public authority (Nasution & Zahrah, 2012). Previous research that is relevant and related to use pattern study in the context of residential green open spaces and parks will be precisely categorized into three sub-topics, which are activities, passive activity, and active activity.…”
Section: Important Measures Of Community Participation On Use Patternmentioning
confidence: 99%
“…Over the years, numerous scholars, researchers and practitioners have studied urban squares to examine their typologies, functions, evolutions and contributions to the city. Studies similar to this are still very relevant today as cities across the globe dynamically grow and undergo change (de Arruda Campos, 2000;Jalaladdini & Oktay, 2012;Nasution & Zahrah, 2012;Vadiati & Kashkooli, 2011). Most of these studies found that the roles of urban squares as a social space are still as important today as they were in history.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Open space is defined as all landscape, hardscape, park, and recreational spaces in a city (Knudsen & Greer, 2008). According to Nasution & Zahrah (2012), successful open space can encourage the feeling of security and comfort of the visitors. Excellent open space is observable from clear movement pattern, the existence of landmark as an orientation, and the use of human scale with good architecture performance (Gehl, 2011;Nasution & Zahrah, 2012).…”
Section: Spatial Planningmentioning
confidence: 99%
“…According to Nasution & Zahrah (2012), successful open space can encourage the feeling of security and comfort of the visitors. Excellent open space is observable from clear movement pattern, the existence of landmark as an orientation, and the use of human scale with good architecture performance (Gehl, 2011;Nasution & Zahrah, 2012). Besides that, the natural elements such as vegetation are also essential to improve comfort and exciting experiences and also to avoid the lousy climate (Ávila et al, 2004;Gehl, 2011).…”
Section: Spatial Planningmentioning
confidence: 99%